A Preliminary Exploration of the Barriers of Sustainable Refurbishment for Commercial Building Projects in Malaysia. (2017) - Masrom, Md Asrul Nasid; Rahim, Mohd Hilmi Izwan Abd; Ann, Siow Chan; Mohamed, Sulzakimin; Goh, Kai Chen
Abstract: Malaysia is one of the developing countries that faced frequent and serious floods in recent years. Sustainable refurbishment seems to play an important role to fight against the climate change. Additionally, sustainable refurbishment approach is the greatest potential ways for reducing carbon dioxide emissions. Existing commercial buildings in Malaysia have been found for one-third of the total electricity consumption. However, the amounts of sustainable refurbished buildings listed in the Green Building Index (GBI) certified are still considerably lower and not fully explored. That is, this research aims to identify the potential barriers that hinder commercial building owners to implement sustainable refurbishment and to determine the drivers that could improve sustainable refurbishment implementation in Malaysia. The qualitative data were collected through semi-structured interview with an experienced commercial building manager in Kuala Lumpur. The content analysis used in utilizing the entire dataset to identify underlying themes presented through the data. The result indicated that the key barriers of sustainable refurbishment are the higher cost of sustainable refurbishment than traditional methods and lacking of sustainable awareness among Malaysian. This preliminary research also found that the drivers that could improve sustainable refurbishment implementation are able to enhance their corporate image and to reduce the environmental impact. The findings of ongoing research can be beneficial for building owners to deliver their refurbishment projects with a green awareness and environmental considerations in the future.